Programming in COBOL/400 - Cooper, James, 1948- 4 0 16; Stern, Nancy B.;Stern, Robert A.; 5 (New York : Wiley, 2002)
A guide to COBOL/400 as used on IBM AS/400 and iSeries Server computer systems, which shows beginners how to write COBOL/400 programs, discusses COBOL/400 program writing theory, and provides complete structured programming examples and many practice problems.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Programming. -- IBM AS/400 (Computer);COBOL (Computer program language);Structured programming.;IBM AS/400 (Computer);COBOL (Computer program language);Computer programming; 20; 2